MITOS DAN REALITAS DALAM CERITA LISAN ASAL MULA MASYARAKAT DESA BAYUNG GEDE - Budiartawan, I Ketut (Humanis; Volume 14. No.1. Januari 2016, 2016)
This study examines the oral story of the origin of the village community Bayung Gede. This study uses the theory of structural and semiotic theory. Methods and techniques used in this study consists of three stages of the provision of data, data analysis stage and the stage presentation of the results of the data analysis. The results of this study have revealed the structure of the narrative is the story of the origin of oral Bayung Gede village community which includes the theme, plot, character and characterization, setting and atmosphere of the place, as well as the mandate. The theme of this oral story building is the theme of creation. The flow used in oral story is advanced groove (progressive) are built by thirteen incidents. People and Personalities consists of main and secondary characters. The main character in this story, the White Apes, then the secondary character, Ida Batara Mount Toh Langkir, The undagi, and Ida Bhatara Semeru, and humans are created by the White Apes. Background story displayed, ie setting the place and atmosphere. Mandate contained in the human oral story is to understand the history itself and the nature of life in the world and so grateful for all the grace. Myths and Realities contained in Community Oral Story Bayung Gede village consists of Myth and Reality Alas Pegametan with Pura Puaji, Tukad Mebaong with Tirta Teak, and Alas Tiing Ivory with Pura Dadap Sakti .
Keywords: oral story, Narrative Structure, Myth and Reality